Sustainability Reporting and Credit Risk Management in the Romanian Banking Landscape - Maria Carmen Huian; Mihaela Curea; Marilena Mironiuc (Amfiteatru Economic)
The paper analyses the association between the reporting of the Sustainable Development Goals (SDGs) and the behaviour of Romanian banks, focusing on the relationship between SDG disclosure scores (both total and across the four sustainability dimensions) and credit risk management practices, measured by the level of credit loss allowances. The study combines content analysis with fixed-effects regressions to examine a sample of Romanian banks spanning the period 2017-2023. The results highlight a positive and significant relationship between the level of SDG reporting - including the environmental, social, and economic dimensions - and the expected credit loss allowances, suggesting that banks actively engaged in sustainability reporting tend to support the financing of emerging sectors, thus exposing themselves to higher credit risk. However, banks appear to mitigate this risk through strong governance practices. The conclusions, relevant for policymakers, emphasise the need for a balanced strategy between commitment to the Sustainable Development Goals (SDGs) and financial stability, highlighting the role of sustainability reporting in enhancing transparency, trust, and the identification of lower-risk sustainable financing opportunities. This research contributes to the existing body of literature by introducing SDG disclosure scores specifically tailored to the banking sector and by employing the Quadruple Bottom Line (QBL) framework, which encompasses the four pillars of sustainability. Moreover, it distinguishes itself by examining the relationship between SDG reporting and credit risk – a relatively underexplored but highly relevant area within the banking industry.